2022
DOI: 10.3390/ijerph19020861
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between VO2 and Muscle Deoxygenation Kinetics and Upper Body Repeated Sprint Performance in Trained Judokas and Healthy Individuals

Abstract: The present study sought to investigate if faster upper body oxygen uptake (VO2) and hemoglobin/myoglobin deoxygenation ([HHb]) kinetics during heavy intensity exercise were associated with a greater upper body repeated-sprint ability (RSA) performance in a group of judokas and in a group of individuals of heterogenous fitness level. Eight judokas (JT) and seven untrained healthy participants (UT) completed an incremental step test, two heavy intensity square-wave transitions and an upper body RSA test consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…Our results also agree with a recent study that assessed judo athletes and untrained subjects [16], where a correlation was found between VT1 with a decrease in the peak power output and accumulated work for the upper body during the repeated sprint ability (RSA). However, when the judo athletes were analyzed separately, the VT1 was not correlated with the RSA [16]. In addition, the VT1 is the only variable correlated with recovery capacity at the end of the test, expressed through HR 1min .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also agree with a recent study that assessed judo athletes and untrained subjects [16], where a correlation was found between VT1 with a decrease in the peak power output and accumulated work for the upper body during the repeated sprint ability (RSA). However, when the judo athletes were analyzed separately, the VT1 was not correlated with the RSA [16]. In addition, the VT1 is the only variable correlated with recovery capacity at the end of the test, expressed through HR 1min .…”
Section: Discussionsupporting
confidence: 93%
“…Using another submaximal variable, corresponding to the intensity of the second threshold, Detanico et al [9] reported a similar correlation between the anaerobic threshold velocity and the number of throws during the SJFT [9]. Our results also agree with a recent study that assessed judo athletes and untrained subjects [16], where a correlation was found between VT1 with a decrease in the peak power output and accumulated work for the upper body during the repeated sprint ability (RSA). However, when the judo athletes were analyzed separately, the VT1 was not correlated with the RSA [16].…”
Section: Discussionsupporting
confidence: 90%
“…as a means of enhancing muscle performance or recovery). The following situations were compared with some control scenarios to evaluate the muscle oxygenation responses and the potential benefits of the tested product or intervention: the use of a tracksuit jacket with heating elements [ 162 ], nonivamide-nicoboxil cream [ 180 ], sports compression garment ( n = 3 for lower limb: tights, calf sleeve, socks; n = 1 for upper limb, forearm) [ 18 , 19 , 31 , 107 ], core and skin cooling [ 136 ], undergoing thigh cooling by a water-circulating pad [ 85 ] and oral supplementation with dietary inorganic nitrate-rich and placebo beetroot juice [ 32 , 33 , 40 , 43 , 63 , 75 , 76 , 131 , 146 , 158 , 183 , 190 , 201 ], supplementation with pomegranate extract and co-supplementation with N -acetylcysteine [ 39 ], protein powder [ 134 ], pre-exercise ingestion of a drink with higher dissolved O 2 [ 135 ], anthocyanin-rich New Zealand blackcurrant supplementation [ 27 ], 1 h after a single dose of mango leaf extract rich in mangiferin and lecithin, or mango leaf extract rich in mangiferin and quercetin, phospholipids addition [ 53 55 ], red spinach extract [ 121 ], citrulline drink/citrulline malate [ 190 , 196 ], l -arginine [ 141 , 143 ], Montmorency cherry polyphenols [ 67 ], eicosapentaenoic acid and docosahexaenoic acid (fish oil) [ 198 ], caffeine intake [ 189 ] and dark chocolate [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Contrarily, this does not appear to be the case for acute dietary nitrate supplementation [ 33 , 63 , 75 , 76 , 158 , 183 , 190 ], citrulline [ 190 , 196 ], l -arginine, red spinach extract [ 121 ], dark chocolate [ 181 ] and caffeine [ 189 ]. Additionally, mechanical ergogenic aids like compression clothing [ 18 , 19 , 31 , 107 ] tend to increase blood flow and muscle oxygenation, especially at rest. With regard to physiological ergogenic aids, techniques like blood flow restriction [ 12 , 14 , 147 149 , 191 , 192 ], voluntary hypoventilation at low lung volume [ 17 , 34 , 88 , 89 , 151 ], electrical muscle stimulation [ 138 , 144 , 173 , 184 , 197 ] and dynamic stretching [ 193 ] typically alter the muscle oxygenation response; however, the effects of other interventions like photobiomodulation therapy [ 105 ] or immersion in water [ 21 , 85 , 94 , 95 ] are less certain.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the articles published in this Special Issue focused on the relation between physical performance and physiological and morphological features [13][14][15][16]. Four papers investigated body composition in sports practice [17][18][19][20], while two articles evaluated new strategies aimed at improving and monitoring the recovery phase after the exercise [21,22].…”
Section: Published Manuscriptsmentioning
confidence: 99%